Modelo pedagógico constructivista en el proceso de la comprensión lectora en estudiantes de séptimo año de educación general básica paralelo “b” de la Unidad Educativa Ángel Polibio Chaves de la ciudad de Guaranda. - Camacho Mendoza, Kathleen Carolina (2022)
The present investigative study is based on analyzing and publicizing the current process of the students in their seventh year of EGB parallel "B" about the reading comprehension carried out through the Ángel Polibio Chaves Educational Unit, by which, once the current context of the course in question has been studied, it is intended to propose teaching strategies that guide and help in the improvement of reading for the development of abilities and skills for the students in the class. This research will allow building a relationship between the teaching model and the educational community, in which the specific contents for its execution can be determined, which will have repercussions on the adequate development for the improvement of reading comprehension in students. It should be noted, for the development of this research project, that the background and problem was raised in the first instance. Latter, also, the description of the problem and formulation of the problem is carried out, then, performs the justification, objectives, general objective and specific objectives, followed by the theoretical framework, which covers the scientific theory, legal theory and referential theory, Another aspect to highlight is the methodological framework in which the approach is executed of the investigation, design or type of study, the methods that were used in the investigation, techniques and instruments of data collection, the survey, interview, the population, sample and the processing of information, Also, to perform the analysis and interpretation of results through a matrix and conclusions. Finally, a proposal was carried out which contains the theme, objective, general objective, specific objectives, development, bibliography and annexes; It is worth mentioning that through this proposal, aspects that help and promote the improvement of the reading process in the school environment are presented.